More is not always better: Non-linear effects in crowdfunding - Thomas Niemand; Sascha Kraus; Martin Angerer; Ferdinand Thies; Alicia Mas-Tur (International Journal of Quality Innovation, 2019)
This research focuses on crowdfunding project features and its relation with the success of this project. The main purpose is to improve probability of success of crowdfunding projects. One can argue that "more is always better" resulting in attempts of daily updates. Contrarily, backers may be weary of numerous updates to work through, indicating a possible wear-out effect, implying the existence of an optimal level of updates. Our preliminary results show that previous research, built upon linear modeling, widely ignores important aspects of the relationship between key variables. We therefore picked six key variables that were previously marked as success drivers in crowdfunding and found most remarkably that none of the six variables clearly follows a linear pattern. These findings call for further investigation of the non-linear patterns within crowdfunding research.
Keywords: 650; Crowdfunding; Linear model; Non-linear mode